2018
DOI: 10.1038/s41598-018-30041-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal quantification of mating system parameters in a coastal Douglas-fir seed orchard under manipulated pollination environment

Abstract: Seed orchards main function is delivering breeding programs’ gains in the form of genetically improved seedlings. They are unique experimental populations, perfectly suited for studying various pollination environments (natural or otherwise), affecting their mating system parameters. Here, under different pollination environment (natural and intrusive (pollen augmentation and/or bloom-delay)), the mating system of a second generation, wind-pollinated, coastal Douglas-fir (Pseudotsuga menziesii var. menziesii (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…In accordance with these results, Slavov et al ( 2005) also reported low levels of selfing ranging from 1 to 2.3% in a non-isolated open-pollinated Douglas fir seed orchard, located in Oregon, USA. However, within a Canadian seed orchard, higher selfing rates ranging from 12 to 17% were observed (El-Kassaby et al 2010; Kess and El-Kassaby 2015; Korecky and El-Kassaby 2016; Lai et al 2010;Song et al 2018). These were explained by strong female fertility variation and a strong correlation between female reproductive success and selfing rate (El-Kassaby et al 2010).…”
Section: Selfingmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with these results, Slavov et al ( 2005) also reported low levels of selfing ranging from 1 to 2.3% in a non-isolated open-pollinated Douglas fir seed orchard, located in Oregon, USA. However, within a Canadian seed orchard, higher selfing rates ranging from 12 to 17% were observed (El-Kassaby et al 2010; Kess and El-Kassaby 2015; Korecky and El-Kassaby 2016; Lai et al 2010;Song et al 2018). These were explained by strong female fertility variation and a strong correlation between female reproductive success and selfing rate (El-Kassaby et al 2010).…”
Section: Selfingmentioning
confidence: 99%
“…Slavov et al (2005) report pollen contamination rates ranging from 31 to 41.3% in Oregon (USA), but this estimate does not only include pollen from outside the seed orchard but also from neighbouring blocks. For the Canadian seed orchard Kess and El-Kassaby (2015), Korecky and El-Kassaby (2016), Lai et al (2010) and Song et al (2018) reported contamination rates of 10-18% despite several measures taken to prevent pollen contamination, and up to 28% under natural conditions. These considerably higher rates of pollen contamination can most likely be explained by the location of the different seed orchards.…”
Section: Pollen Contaminationmentioning
confidence: 99%
“…Seed production in hoop houses (greenhouse-like structures), orchards located outside the native range, supplemental mass pollination and bloom delay (e.g. water cooling) have been suggested as solutions to reduce or eliminate pollen contamination 1,57 . However, when orchards are grouped together in a single location for ease of management, care must be taken to ensure weather conditions and all available silvicultural options are considered.…”
Section: Discussionmentioning
confidence: 99%
“…The different genetic groups for maternal and paternal contributions is expected, this is supported by the research results of mating dynamics in seed orchards. Evidence was shown on the presence of pollen contamination in seed crop in the range of 10% [29] to 90% [30] with indicating a relatively stable seasonal variability [29, 31].…”
Section: Discussionmentioning
confidence: 99%